2021
DOI: 10.3390/nu13093144
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Aerobic-Resistance Training and Broccoli Supplementation on Plasma Dectin-1 and Insulin Resistance in Males with Type 2 Diabetes

Abstract: Background: This study aimed to evaluate the effects of a combination of aerobic-resistance training (CARET) and broccoli supplementation on dectin-1 levels and insulin resistance in men with type 2 diabetes mellitus (T2D). Methods: Forty-four males with T2D were randomly allocated to four groups (n = 11 each group): CARET + broccoli supplement (TS), CARET + placebo (TP), control + broccoli supplement (S), and control + placebo (CP). CARET was performed three days per week for 12 weeks. TS and S groups receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…The selection process is presented in the flow diagram (Figure 1). Ten studies met the inclusion criteria (28)(29)(30)(31)(32)(33)(34)(35)(36)(37). The studies were published between 2006 and 2021.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The selection process is presented in the flow diagram (Figure 1). Ten studies met the inclusion criteria (28)(29)(30)(31)(32)(33)(34)(35)(36)(37). The studies were published between 2006 and 2021.…”
Section: Resultsmentioning
confidence: 99%
“…Saeidi et al ( 35 ) investigated the effects of broccoli sprouts powder (B) in addition to physical training (combined AE/RT). The control groups received training + placebo, B only or placebo only.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dysregulations in CLRs, including Dectin-1, have been associated with the development of inflammatory disorders, such as diabetes mellitus [ 19 , 20 , 21 ]. Cortez-Espinosa et al reported that abnormal expression and function of the Dectin-1 receptor in T2D patients with poor glycemic control [ 9 ].…”
Section: Discussionmentioning
confidence: 99%